Snack Supply Information System at UD Bunda Ida Using the EOQ Method - Azrial Pratama; Samsudin (Politeknik Piksi Ganesha Indonesia, 2026)
This research aims to design an integrated inventory information system with the Economic Order Quantity (EOQ) method, equipped with safety stock and reorder points, to assist stores in optimizing inventory control. The EOQ method is used to determine the number of orders that are economical so that it can minimize the total cost of inventory. The developed system not only calculates EOQ, but also manages inventory data in real-time, provides notifications of near-expired products, and re-order recommendations. This study fills the gap from previous studies that are still limited to semi-manual or unintegrated systems. The design results show that the EOQ-based information system is able to improve the efficiency of inventory management, reduce the risk of overstock and stock shortages, and support more accurate decision-making. Thus, this system is expected to help UD Bunda Ida in providing optimal service to consumers while increasing business profits.